Sri Lanka : Seventh Review under the Stand-By Arrangement and Requests for Waivers of Nonobservance of Performance Criteria, Extension of the Arrangement Period, Rephasing of Purchases, and Establishment of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses Sri Lanka's seventh review under the Stand-By Arrangement and requests for waivers of nonobservance of performance criteria. The strong economic recovery continued in 2011, with growth estimated at 8u percent. Activity was robust across all sectors, supported by healthy exports and strong growth in domestic demand. Agriculture recovered from flooding early in the year, and is expected to grow at 6 percent. The rupee came under increasing downward pressure in the second half of 2011, especially after the size of the trade deficit became apparent and started to weigh on sentiment.